Analysis of contemporary value and influence of intangible cultural heritage based on online review mining. - Qiaoyun Xu; Yan Xu; Chao Ma (PLoS ONE)
Purpose The development of new media has enabled intangible cultural heritage to be disseminated through online platforms and attracted the attention of many contemporary young people. Classification and discussion on the value of intangible cultural heritage is an important way to help the inheritance and dissemination. Design/methodology/approach Real online reviews were collected based on the Bilibili website as the research data source. A text-based BiGRU-Attention model was conducted to achieve value recognition and classification, and keyword statistics and topic analysis were performed for topic discussion among comments. Findings Using the BiGRU-Attention model to classify intangible cultural heritage's contemporary values has a performance with precision, recall, and F1 score of more than 77%, the category of CVP (Cultural Value Perception) has the best classification performance. Through the topic analysis of comments and keywords, the cultural value of intangible cultural heritage is its core connotation, social value is the main purpose, and economic value is the power source. Originality A BiGRU-Attention model based on BERT word embedding is proposed to achieve a text contemporary value perception recognition method based on user-generated content.